THE BALKAN MOUNTAINS PALEOZOIC GOLD DEPOSITS - Mladenova, V.; Kerestedjian, T.; Dimitrova, D. (Bulletin of the Geological Society of Greece, 2004)
A number of Paleozoic gold deposits are situated in the Hercynian terrains of the Balkan Mountain. On Bulgarian territory Govezhda and Svishti Plaz deposits are the most important ones. Neresnitza, Blagoev-Ka nen and Osanitza deposits are located in the Serbian part of the Balkan Mountain. All these deposits are hosted in the Pre-Alpine basement of the Balkanide zone. The orehosting structures are veins, lenses and mineralized fissures related to tension and shear faults. The structural characteristics of the ores are an evidence for tectonic control and tectonic activity during the ore deposition. All stages of ore deposition were accompanied by strong fracturing of already deposited minerals and subsequent precipitation of next portion. The economically important mineral in all these deposits is the native gold, with variable Ag contents. In the two Bulgarian deposits the main ore minerals are arsenopyrite and pyrite. Arsenopyrite is not reported for Serbian deposits, but scheelite is a main mineral there instead. Based on mineral associations, three possible genetic concepts of Au deposition could be expressed. 1) The gold is genetically associated with arsenopyrite and pyrite from stage 1 (Fe-As- Au+W). It is primarily deposited as invisible gold in these minerals. During the next stage of sulfide deposition driven by induced heating, it is remobilized and redeposited in cracks, formed during the cataclastic events of this stage. 2) The gold is genetically connected to the stage 2 (Pb-Zn-Cu-Ag- Au). 3) Dual generation of gold related to both stages 1 and 2. All Balkan Paleozoic gold deposits show lots of similarities to mesothermal gold deposits in shear zones in Archaean greenschists terrains in Canada, Western Australia and Africa, as well as to Hercynian gold deposits in France and Portugal. The similarity especially concerns their connection to granodiohtic magmatism, the mineral parageneses and the gold occurrence and its associations. Despite that the mining in the Balkan gold deposits is already closed, they still have nonexplored and non-operated reserves